1988
DOI: 10.1063/1.99941
|View full text |Cite
|
Sign up to set email alerts
|

New approach to the atomic layer epitaxy of GaAs using a fast gas stream

Abstract: A new growth method has been developed for the atomic layer epitaxy of GaAs. The gas system was based on a conventional metalorganic vapor phase epitaxial system but the decomposition of methylgallium was suppressed in the stagnant layer by using a fast pulsed gas stream from a jet nozzle. The method enabled us to grow high purity epitaxial layers with a clear self-limiting mechanism even at 560 °C. The variations in the growth rate with respect to various growth parameters were explained by the rate equations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…We have developed an ALE method (pulsed-jetepitaxy: PJE) for III-V compounds, based on a vapor-phase system using metalorganic compounds and hydride [8]. PJE has enabled us to grow homoepitaxial layers of III-V compounds with an ideal self-limiting mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed an ALE method (pulsed-jetepitaxy: PJE) for III-V compounds, based on a vapor-phase system using metalorganic compounds and hydride [8]. PJE has enabled us to grow homoepitaxial layers of III-V compounds with an ideal self-limiting mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…A rate equation is useful for the analysis of the growth mechanism in ALE [6,7]. Let 1/t s be the arrival rate of (MeCp) 2 Mn molecule on the growing surface.…”
Section: Resultsmentioning
confidence: 99%
“…The carrier gas was hydrogen. The pulsed-jet-epitaxy (PJE) was used in the ALE [7]. The PJE reactor had a chimney-type structure where the carrier gas and reactants were introduced from the bottom and exhausted through the top by high capacity vacuum pumps.…”
Section: Methodsmentioning
confidence: 99%
“…7 The SPA method is especially successful in investigating monolayer (ML) growth of compound semiconductors because of its high sensitivity to reflectivity changes on surfaces covered with different chemicals. Many studies of monolayer growth at temperatures ranging as high as 700°C have been reported using various methods, [8][9][10][11] however most of the SPA studies of GaAs growth have been reported at temperatures below 500°C on GaAs substrates. 5,6,[12][13][14][15][16][17] In this work, we report an SPA study of MOCVD GaAs monolayer epitaxy by interrupted growth at 650°C, which is the highest temperature studied so far by SPA to our knowledge.…”
Section: Introductionmentioning
confidence: 99%